The epic of Hang Tuah - Muhammad Salleh 1942-; Robson, Rosemary (Malay great work series, 2014)
Written between 1641 and 1739, this epic reflects the aspirations, ability, attitudes, culture and manner of the Malay people who were respected and acknowledge by foreigners long before the Portuguese invasion of Melaka. It was Hang Tuah who said, "The Malay will never vanish from this world."